Effect of in content on thermoelectric performance of InxGa1-xN alloys: Hybrid density functional theory study based on realistic models - Aroussi, H. C.; Marana, N. L. [UNESP]; Hamdache, F.; Houaria, R.; Bahlouli, S.; Casassa, S. (Elsevier B.V., 2021)
In this study, first-principles periodic calculations with localized Gaussian type orbitals within a hybrid density functional theory approach were performed to study the electronic, structural, thermodynamic, and transport properties of InxGa1-xN nitride alloys. The compositions were modeled in the range of 0.06 < x < 0.87 using a 32-atom supercell. According to previous studies, significant composition-dependent gap bowing occurs for both the lattice parameters and energy band gap. Our study of the thermodynamic stability indicated a notable trend toward spinodal decomposition. Infrared spectra are used as fingerprints to uniquely determine the composition and structure of alloys. Based on the transport properties calculated in the present study (Seebeck coefficient, power factor, and figure of merit), the ternary structure with approximate to 20% In is the optimal thermoelectric material and preliminary investigations confirmed that the transport properties can be altered by point defects.